Comparative time-resolved photoemission from the Cu(100) and Cu(111) surfaces - Ambrosio, Marcelo J.; Thumm, Uwe (My University, 2016)
Motivated by the striking dependence of the valence electronic structure of transition metal surfaces on their crystallographic orientation, and by emerging experiments on laser-assisted extended ultraviolet (XUV) photoemission from solid surfaces, we calculate photoemission spectra from Cu(100) and Cu(111) surfaces as a function of the photoelectron final kinetic energy and the delay between the ionizing attosecond XUV pulse train and assisting infrared (IR) laser pulse. Our numerical simulations predict distinct differences in delay-dependent photoelectron energy distributions and photoemission time delays for Cu(100) and Cu(111) surfaces. These differences can be scrutinized experimentally with existing technology in a suggested in situ comparative RABBITT (reconstruction of attosecond beating by interference of two-photon transitions) configuration by placing the two surfaces on a sliding platform while keeping all optical components and pathlengths fixed. Our calculations also show that the inclusion of the Fresnel-reflected incident IR pulse at the metal-vacuum interface modifies photoelectron spectra and photoemission time delays in a characteristic way that reveals the degree of spatial location of the initial electronic states.